Impact of Increasing in Production Capacity of CPO Downstream Industries on Competitiveness and Welfare of Oil Palm Farmers in Indonesia - Novindra Novindra; Bonar M Sinaga; Sri Hartoyo; Erwidodo Erwidodo (International Journal of Oil Palm, 2019)
Indonesia is the largest country in exporting crude palm oil (CPO) to the world market. However, the production capacity of the CPO downstream industries in Indonesia must continue to be increased, bearing in mind that Indonesia also imports CPO derivative products. In addition, oil palm plantations in Indonesia still face environmental and social issues, such as: deforestation, damage to peatlands, destruction of wildlife habitat (such as orang-utans), and land tenure conflicts. In this connection, Indonesia needs to continue to develop the CPO downstream industries that can increase added value and foreign exchange, absorb employment, and address environmental and social issues. Therefore we need appropriate government policies to support the development of the CPO downstream industries. The purposes of writing this paper were to analyze the factors that influence CPO demand by the CPO downstream industries (ie: palm cooking oil, margarine and soap industry) in Indonesia, and to evaluate the impact of facilitation policy that increasing production capacity of the CPO downstream industries on the CPO competitiveness of Indonesia-Malaysia and the palm cooking oil, margarine and soap competitiveness of Indonesia, as well as the welfare of oil palm farmers in the 2015-2017 period. This paper was part of the dissertation research results that using the CPO industry econometrics model. The dissertation model specification is a dynamic simultaneous equation consisting of 71 behavioral equations and 51 identities, while the model was estimated and simulated using the 2SLS and Newton methods. The results showed that the production capacity of the CPO downstream industries affected CPO demand by the CPO downstream industries. Furthermore, if the production capacity of CPO downstream industries (palm cooking oil, margarine, soap, biodiesel and others) increases, it will increase the Indonesian competitiveness in export CPO and its derivative and welfare of oil palm farmers in Indonesia.